Cost-effectiveness of infant hypoallergenic formulas to manage cow's milk protein allergy in France - Ana Teresa Paquete; Rui Martins; Mark P. Connolly; Marie Meulle; Nítida Pastor; Grégoire Benoist; Patrick Tounian (Taylor & Francis Group, 2023)
ABSTRACTBackground Clinician's choice of hypoallergenic formulas in the first-line management of cow's milk protein allergy (CMPA) should be informed by evidence on clinical efficacy and cost-effectiveness.Objective We compare the cost-effectiveness of amino acid-based formula (AAF), extensively hydrolyzed casein formula with Lactobacillus rhamnosus Gorbach Goldin (EHCF+LGG), extensively hydrolyzed whey formula (EHWF), and rice hydrolyzed formula (RHF) in non-breastfed children in France.Methods Immunotolerance and atopic manifestations' prevalence were based on a prospective non-randomized study with a 36-month follow-up. Resource utilization was sourced from a survey of French clinicians, and unit costs were based on national data. Costs and health consequences were discounted at 2.5% annually. Results were reported using the Collective and French National Health Insurance perspectives.Results Children receiving EHCF+LGG were predicted to require less healthcare resources, given their reduced prevalence of CMPA symptoms at 3 years. In the base case, EHCF+LGG led to savings of at least €674 per child compared to AAF, EHWF, and RHF at 3 years, from both perspectives. Nutrition had the highest economic burden in CMPA, driven by hypoallergenic formulas and dietetic replacements costs. Results were robust to one-way and probabilistic sensitivity analyses.Conclusions EHCF+LGG was associated with more symptom-free time, higher immune tolerance, and lower costs.